Notes in colombian herpetology, i: a new snake of the genus rhadinaea (1943)
The following brief contribution to the Herpetology of Colombia is; the first of a projected series which I hope to make under the auspices of the Instituto de Ciencias Naturales de la Universidad Nacional de Colombia and of the Commitee for Inter-American Artistic and Intellectual Relations. For the opportunity to make this and other studies I am indebted to the Director of the Instituto, Dr. Armando Dugand, and to the Committee. I also wish to make similar aknowledgements to Hermano Nicéforo Maria of the Instituto de La Sane for the privilege of being allowed to examine the specimens in his charge.   I hope to be able to make a revision of the whole group of Colombian snakes allied to Rhadinaea. I here offer only the description of a rather striking new form, which may be called